Cis-Hetero-Misogyny Online - Richardson-Self, Louise (Ethical theory and moral practice, 2019)
This article identifies five genres of anti-queer hate speech found in The Australian's Facebook comments sections, exposing and analyzing the ways in which such comments are used to derogate cisgender and (often) heterosexual women. One may be tempted to think of cis-het women as third-party victims of queerphobia; however, this article argues that these genres of anti-queer speech are, in fact, misogynistic. Specifically, it argues that these are instances of cis-hetero-misogynistic hate speech. Cis-hetero-misogyny functions as the "law enforcement branch" of a cis-hetero-patriarchal gender order. Given the existence of such an order, it is clear that cis-het women's liberation is inextricable from queer liberation (and vice versa). This article argues that to facilitate allyship and challenge this gender orderthe order that elicits such hate speech actswe need an epistemological revolution in the way we recognize and re-cognize human difference.